Arthrogryposis multiplex congenita definition: Update using an international consensus‐based approach. Issue 3 (26th August 2019) - Cachecho, Sarah; Elfassy, Caroline; Hamdy, Reggie; Rosenbaum, Peter; Dahan‐Oliel, Noémi
Abstract: Arthrogryposis multiplex congenita (AMC) has been described and defined in thousands of articles, but the terminology used has been inconsistent. Some have described it as a diagnosis or syndrome, others as a term or clinical finding. This lack of common language can lead to confusion in clinical and research communities. The aim of this study was to develop a consensus‐based definition for AMC using international expert opinion. A consensus‐based definition will help harmonize research and clinical endeavors and will facilitate communication among families, clinicians, and researchers. This article describes the methodology used leading to a proposed definition of AMC. First, a literature review was conducted to identify AMC definitions used in included studies. The most commonly used words in the definitions were extracted. Second, a group of eight experts in AMC was selected to identify elements considered critically important to the definition of AMC. Third, based on these critical elements and the literature review, a definition was drafted by the research team. Fourth, a modified Delphi consensus process was conducted using electronic surveys with 25 experts in the field of AMC from eight countries. Survey results were analyzed quantitatively and qualitatively and drafts were modified accordingly. Three rounds of surveys were completed until consensus was reached on a definition of AMC. An annotation of this definition, developed by a panel of international experts, is provided in a separate manuscript in this special issue.